PERANAN TUNGKU TIGO SAJARANGAN DALAM MENGATASI PERKAWINAN SESUKU MENURUT HUKUM ADAT DI NAGARI SUNGAI BULUAH KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Pratama, Iqbal Sonta; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Minangkabau society is one of the largest ethnic in Indonesia that use the system matrilinealkinship (matrilineal). Minangkabau society envisage at the matter of marriage as a very important event,because marriage is the successor of the descent. Marriage in matrilineal society is exogamy, marriageconsists of the group is not justified because they all are descended from a group of blood-reltive. If theprospective spouses to marriage is prohibited by customary law Minangkabau it will be sanctioned by thetraditional leader known as Tungku Tigo Sajarangan. The purpose of this thesis is; First, to find out therole of traditional leaders in overcoming that tribal marriages under customary law in Nagari SungaiBuluah Batang Anai District of Padang Pariaman; Second, to find out the marital dispute settlementagainst tribesmen by Tungku Tigo Sajarangan in Nagari Sungai Buluah Batang Anai District of PadangPariaman.This type of research is the type of juridical empirical research, can be a study of the identificationlaw (common law), in which this is done to determine the unwritten law based on the applicable law insociety, as well as research on the effectiveness of law that addresses how the law operates in society. Thisresearch requires the researcher to know the science of law, social sciences and memeiliki knowledge insocial science research.From the research, there are two main things that can be inferred. First, the role of traditionalleaders in overcoming that tribal marriages under customary law in Nagari Sungai Buluah Batang AnaiDistrict of Padang Pariaman in this case are the responsible and obliged to preserve the members of thetribes and their area. In a customary term, namely; Kusuik manyalasai, Karuah mampajaniah, Tumbuahnyoditanam, Tingginyo dianjuang, Gadangnyo diamba. Second, the marital dispute settlement againsttribesmen by Tungku Tigo Sajarangan in Nagari Sungai Buluah Batang Anai District of Padang Pariamancarried out in the form of meetings attended by all Ninik Mamak, Alim Ulama and other indigenous leaders.Executed with several stages of completion, namely the imposition of penalties, payment of the fine and anapology. The sanction was fined one or two head of cattle such as cows, goats or buffalo, were expelledfrom their homes and should no longer re-settled in villages as husband and wife. Performers that tribalmarriage may return home with a record already doing sanctions and received forgiveness from alltraditional and community leaders.